Adinopsis nippon, a new species of marsh-dwelling rove beetle (Coleoptera: Staphylinidae: Aleocharinae: Deinopsini) from Japan, with an annotated catalogue of Adinopsis species of the world - Maruyama, Munetoshi; Kamezawa, Hiromu (Zootaxa, 2013)
Adinopsis nippon sp. n. is described from Japan and represents the first discovery of the genus Adinopsis in the temperate zone of the East Palearctic region. It is closely related to A. myllaenoides (Kraatz) known from North and South America and is placed in the myllaenoides species group. An annotated catalogue of the world species of Adinopsis is presented.